2017
DOI: 10.1007/s13534-017-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

First demonstration of velocity selective recording from the pig vagus using a nerve cuff shows respiration afferents

Abstract: Neural interfaces have great potential to treat disease and disability by modulating the electrical signals within the nervous system. However, whilst neural stimulation is a well-established technique, current neural interfaces are limited by poor recording ability. Low signal amplitudes necessitate the use of highly invasive techniques that divide or penetrate the nerve, and as such are unsuitable for chronic implantation. In this paper, we present the first application of the velocity selective recording te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…) of the vagus nerve. Preclinical studies for chronic vagus nerve electrodes have been successfully conducted in large animal models (Zhang et al 2009;Ardell et al 2017;Hamann et al 2013;Metcalfe et al 2018;Valdés-Cruz et al 2002) and in rats (Somann et al 2017;McCallum et al 2017;Grimonprez et al 2015;Li et al 2004;Khodaparast et al 2016). Thus far, no studies for chronic mouse vagus nerve interfacing have been reported.…”
mentioning
confidence: 99%
“…) of the vagus nerve. Preclinical studies for chronic vagus nerve electrodes have been successfully conducted in large animal models (Zhang et al 2009;Ardell et al 2017;Hamann et al 2013;Metcalfe et al 2018;Valdés-Cruz et al 2002) and in rats (Somann et al 2017;McCallum et al 2017;Grimonprez et al 2015;Li et al 2004;Khodaparast et al 2016). Thus far, no studies for chronic mouse vagus nerve interfacing have been reported.…”
mentioning
confidence: 99%
“…As the separation between the stimulation and recording sites increases, the individual action potentials that form the eCAP will spread out in space and time; although this would enable a finer level of discrimination it would also reduce the overall SNR. The limit of this case might be considered the physiological neural activity, which we have discussed previously [7].…”
Section: Discussionmentioning
confidence: 99%
“…using hook electrodes in rat [6]. This work was further developed by recording respiration afferents from a much larger nerve (the right vagus) in pig, using a chronically implantable cuff electrode [7]. In this paper, we present an analysis of the electrically evoked potentials within pig vagus, including a discussion on the validation of previous approaches, and evaluate the effectiveness of velocity discrimination as a tool for online neural recording and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep learning-based algorithms have shown their efficiency in numerous fields and tasks, especially in classification. Starting with the year 2012 award winning AlexNet [22] from ILSVRC's ImageNet, deep learning-based methods have shown high performance in cases of large 1-dimensional and 2-dimensional data analysis and classification [23]. Its application in the field of neural signal analysis can also be seen.…”
Section: Introductionmentioning
confidence: 99%